The Analysis Of Implementation Of Permit To Work at Height in the Projects PT. X year 2023 - Saragih, Kurniawan Syahrimbun; Dewi, Fitri; Kafit, Muhammad (Jurnal Ilmu Kesehatan, 2024)
World developments influence to all sectors, including the development sector which is also increasingly rapid and with the application of increasingly sophisticated technology, the application of Occupational Health and Safety is one of the main requirements for work that must be taken into account. is one of the contractors engaged in the construction sector where its activities cannot be separated from working at heights, So it is necessary to carry out observations and observations in the field regarding "Analysis of the Implementation of the Permit to Work System for Height Work on the Project of PT. X year 2023”. The research method used in this research is qualitative-descriptive, because this type of research is the most appropriate for analyzing the implementation of the permit to work system using interviews, observations and also document review. From the results of research on the implementation of a permit to work system for work at height on the Project of PT. X, starting from the stages of preparation consisting of coordination, planning, assessment, isolation, prevention, validity period, signature, process stages consisting of permit, revalidation, suspension, action in emergency, monitoring and closing stages consisting of returning permit to Work, Site Inspection, Cancelation of Overrides, Return to service, Log/record it is known that the implementation of the three stages of the Permit to work System for work at height on the Project of PT. X has done quite well. Even though the implementation is good, there are several stages that still need to be improved because they are not in accordance with the standards of MoM Regulation No. 9 year 2016 concerning safety for work at heights. The recommended to improve such as coordinating the agenda for briefings, risk assessments being distributed in the work area, work area restrictions being improved, not only police lines, PPE checks being carried out before and after work, checking first aid equipment, work permit displays being carried out even outside of building, telling workers how to process work permits for extensions and returns, having checklists for monitoring during work and after work is completed, checking equipment when it is returned, and for the rest it is good enough and hopefully it can be maintained.